Analyzing Students’ Perceptions of Online Learning Models in Higher Education: An Exploratory Approach - Khumalo, Mandla (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examined online teaching models ascertaining both the advantages and disadvantages involved in implementing these strategies. It also explored future implications of this phenomenon. There have been different worldly transformations including the ones caused by COVID-19 which led to learning institutions adopting online learning and teaching models. While there are notable advantages in the usage of online learning, this phenomenon also presents new challenges for both learners and lecturers. This study explored both aspects of the transformation in an exploratory format from a students’ perspective. Students are the prime beneficiaries of online learning models and therefore it is imperative to investigate their viewpoints in order to get full insights into the phenomenon. Data was collected from participants enrolled in online higher education courses using a purposive data collection method. Semi structured interviews were conducted using a questionnaire. The results suggest that acceptance and adoption rates of online learning are increasing. The adoption and effectiveness of online learning varies significantly among students and this is mainly based on access and affordability of technology, access to the internet, and students’ preferences. Some potential students are not privileged enough to have access to technological tools and others lack the skills necessary to maneuver through online content. However for those with access to technology, online learning was viewed as significantly beneficial and students have a positive attitude towards online learning models.